Analysis of a miR-148a Targetome in B Cell Central Tolerance - Ma, Fengge; Zhan, Yating; Bartolomé-Cabrero, Rocío; Ying, Wei; Asano, Masahide; Huang, Zhe; Xiao, Changchun; González-Martín, Alicia (Frontiers in Immunology, 2022)
A microRNA (miRNA) often regulates the expression of hundreds of target genes. A fundamental question in the field of miRNA research is whether a miRNA exerts its biological function through regulating a small number of key targets or through small changes in the expression of hundreds of target genes. We addressed this issue by performing functional analysis of target genes regulated by miR-148a. We previously identified miR-148a as a critical regulator of B cell central tolerance and found 119 target genes that may mediate its function. We selected 4 of them for validation and demonstrated a regulatory role for Bim, PTEN, and Gadd45 alpha in this process. In this study, we performed a systematic functional analysis of the other miR-148a target genes in in vitro and in vivo models of B cell central tolerance. Our results show that those additional target genes play a minimal role, if any, in miR-148a-mediated control of B cell central tolerance, suggesting that the function of miRNAs is mediated by a few key target genes.